From Uncle Tom to Nat Turner: An Overview of Slavery in American Film, 1903-2016 - Melvyn Stokes (Transatlantica)
This article analyses the representation of American slavery in film over more than a century. It argues that the filmic construction of slavery has always been controversial. As American cinema evolved, the dominant filmic view of slavery presented it as a benign institution. Yet, it is noted, even in films such as The Birth of a Nation (1915) and Gone with the Wind (1939), there were sequences that challenged this interpretation and hinted at the brutality and exploitation of the institution. In the aftermath of World War II, a more critical view of slavery began to emerge on film. Yet slavery itself was not a popular theme with audiences, as demonstrated by the reception of Amistad (1997). This seemed to change in the second decade of the twenty-first century when three films—Lincoln (2012), Django Unchained (2012), and 12 Years a Slave (2013)—dealt critically with slavery while also attracting a mass audience. The reasons for the success of these films—and the failure of The Birth of a Nation (2016)—are discussed in relation to broader changes in American social and cultural attitudes.